A Simplified Synthesis of HNDB (Albiducin A) and Calidiol A - Stell, Matthew; Sandoval, Marissa; Ramirez, Santiago; Darragh, Kathy; Schulz, Stefan (Synlett, 2025)
A short, gram-scale synthesis of 2-hydroxy-6-nona-1,3-dienylbenzaldehyde (HNDB, albiducin B) starting from 3-hydroxyphthalic anhydride is reported that also allows access to the fungal metabolite calidiol A. HNDB is needed to understand the ecology of certain euglossine bees that actively search for this compound for uptake. The original source of HNDB is unknown.
Keywords: phenols; aromatic aldehydes; Wittig reaction; diol protection; natural products; solitary bees; pheromones; bee perfume